ANALISIS PENGEMBANGAN SDM PADA UMKM TUM TIM COOKIES & BAKERY SIDOARJO - Prihatiningtyas, Setya; Fatmawati, Rini; Wardani, Citra Dewi Ayu Kusuma; Putri, Kharisma Delia (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2025)
This study aims to describe and analyze human resource development practices in MSMEs Tum Tim Cookies & Bakery in Sidoarjo. With a descriptive qualitative approach, data was obtained through in-depth interviews, participatory observations, and documentation, then analyzed using the thematic techniques of Miles, Huberman, and Saldana. The results showed that HR training was conducted informally, based on hands-on experience in the workplace without any written training procedures or modules. Learning occurs through daily practice guided directly by business owners, in accordance with the principle of experiential learning. Although capable of forming basic skills, a structured evaluation system to measure the effectiveness of training objectively has not been found. Performance appraisals are carried out subjectively and awards are given based on loyalty and work responsibility. Another interesting finding is the implementation of a work culture based on religious values (religion company), where employees are recruited only from among Muslims. This approach strengthens team cohesion and shared values, but also poses challenges related to diversity and inclusivity. This study concludes that human resource development in household-scale MSMEs like this is relational, intuitive, and contextual, but has not been institutionalized systematically. The practical implications of this study include the importance of the preparation of SOPs, training logbooks, and the development of simple evaluation systems that are adaptive to local culture. This study also makes a theoretical contribution in developing an experience and community value-based training model to increase the competitiveness of MSMEs in a sustainable manner